Fixed variant of cutaneous sporotrichosis: A rare entity in non-endemic belt - Das Sudip; Banerjee Gautam; Biswas Indranil (Wolters Kluwer Medknow Publications, 2006)
A sporadic case of sporotrichosis restricted to the primary site of inoculation in a fifty one years old farmer from a non-endemic region of West Bengal has been described. The significance of the report is that most cases of the fixed variant of sporotrichosis had hitherto been reported from the endemic belt of sub-Himalayan region. That the fixed variant is limited to the endemic region is probably a myth.